The Effect of Student Self-Efficacy and Learning Motivation on Student Learning Independence at SMA Negeri 7 Manado - Suyono, Desy (Soedirman Economics Education Journal, 2025)
This research aims to 1) determine the impact of self-efficacy on learning independence, 2) determine the impact of learning motivation on learning independence, and 3) determine the impact of self-efficacy and learning motivation on learning independence. This research applies a quantitative research approach through research methods ex post facto. The population in this study was all class XI students at SMA Negeri 7 Manado for the 2024/2025 academic year, totaling 106 students. The sampling method applied is proportional random sampling. The data analysis techniques used by researchers are classical assumption tests such as normality tests, multicollinearity tests, and heteroscedasticity tests, as well as hypothesis tests such as multiple linear regression, t-test, F-test, and coefficient of determination. The results of this research are 1) Self-efficacy has a positive and significant impact on learning independence, 2) Learning motivation has a positive and significant impact on learning independence, and 3) Self-efficacy and learning motivation together have a significant impact on learning independence. The results of the coefficient of determination test show that self-efficacy and learning motivation contribute 59.3% to learning independence, while another 40.7% is explained by other variables not examined in this research.